DINAMIKA KONFLIK PARTAI GOLONGAN KARYA (GOLKAR) TAHUN 2013-2015 DI PROVINSI RIAU - Maya Friscilia; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The research aims to see the Dynamics of Conflict of the Golkar Party in 2013-2015 In Riau Province, and the focus of this research is how the political dynamics conducted by the Golongan Karya party from 2013 to 2015 until the consolidation phase of the Golongan Karya party. This research uses descriptive qualitative method. Analysis of data presented in the form of qualitative that describes the actual situation in detail and actual by looking at the problem and research objectives. The study was conducted by interviewing informants who really understood with the problems of research that became the object of information that aims to achieve goals and obtain information in this study. This study examines the internal conflicts that occurred in the Golkar Party in 2013-2015. This conflict began with the Government's power along with Golkar that led to totalitarianism, bringing disappointment in society. Therefore, Golkar organizes an extraordinary national deliberation (munaslub) as an effort to fix the Golkar institute. In the munaslub, was elected Setya Novanto as chairman of the Golkar Party. Thus, the existence of Golkar Party continues, although there are some basic changes such as in its vision and mission: open, independent, democratic, moderate, entrenched, and responsive. When examined in terms of institutional, or analysis of the conflict that occurred in the Golkar Party, then it reflects the party only wants to achieve the benefits and personal interests. Keywords: Dynamics, Political Conflict, Political Parties, Leadership